Elemental and isotopic data from from ODP Hole 112-680A, Peruvian Margin - Paula Luiza Fraga-Ferreira (PANGAEA, 2024)
The data are from sediments collected during ODP Expedition 112, borehole 680A, at the Peruvian Margin. The dataset includes concentrations of Al (mg/g), Fe (mg/g), Mn (mg/g), P (mg/g), K (mg/g), Ca (mg/g), Na (mg/g), Mo (μg/g), U (μg/g), N (%), S (%), TOC (%), TC (%), Fe extracted by sodium acetate (%), Fe extracted by sodium dithionite (%), Fe in magnetite (%), Fe in pyrite, δ^1?N ( extperthousand), δ^1^3C ( extperthousand) in the organic fraction of sediments, and δ??Mo ( extperthousand) from 45 different samples. The aim of collecting these data was to investigate how oxygen levels at the seafloor and in the water column fluctuated from the Pliocene to the Pleistocene.